NCIS: Tony & Ziva. Season one [videorecording (DVD)]. - McNamara, John, 1962- (Paramount, 2026)
NCIS: Tony & Ziva places Special Agents Tony DiNozzo (Michael Weatherly) and Ziva David (Cote de Pablo) at the front and center of the action. Once presumed dead in a mortar attack, Ziva is very much alive, and living in Paris, where she and Tony, her fellow former agent, and on-again, off-again lover, are co-parenting their young daughter, Tali. When Tony's security company is attacked, the family must go on the run across Europe, attempt to piece together who's after them, and maybe even learn to trust each other again so they can finally achieve a kind of happily ever after -- unconventional though it may be."--Disc container.